Bimetallic MnCo selenide yolk shell structures for efficient overall water splitting. (10th November 2018) - Mei, Gui; Liang, Hanfeng; Wei, Binbin; Shi, Huanhuan; Ming, Fangwang; Xu, Xun; Wang, Zhoucheng
Abstract: In this work, we systematically investigate and compare the activity of MnCo-based electrocatalysts (i.e. selenide, oxide, and hydroxide) for the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline solutions. The result indicates that the selenides are oxidized upon OER and the surface generated oxides are the real OER active species. The MnCo selenides exhibit a significantly enhanced performance as compared to the oxide and hydroxide though the real active OER species of these three catalysts are essentially the same. The superior activity of MnCo selenides could be attributed to the high intrinsic conductivity and the high surface active area. Further, the synergy between Mn and Co lowers the energy barrier for catalysis and helps to stabilize the material. The bimetallic MnCo selenides with yolk shell structures possess the optimal electrochemical performance with a low cell voltage of 1.66 V at the current density of 50 mA cm −2, outperforming most of the earth-abundant electrocatalysts. Our work provides a better understanding of the active species of metal selenides and the origin of the performance disparity between selenides (-derived oxides) and oxides electrocatalysts. Graphical abstract: Highlights: The electrolyzer with both Mn-Co-Se electrodes drives 50 mA cm −2  at a cell voltage of 1.66 V. Almost 100% Faradaic efficiency of HER and OER is achieved. The surface generated oxides are the real active species of selenides for OER. The synergy between Mn and Co lowers the energy barrier for catalysis and stabilizes the material.